Hardmetal and cutting tools

JP7645360B2Active Publication Date: 2025-03-13KYOCERA CORP
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2023508859
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-03-25
Filing Date
2022-03-01
Publication Date
2025-03-13
Estimated Expiration
2042-03-01

Smart Images

  • Figure 0007645360000003
    Figure 0007645360000003
  • Figure 0007645360000004
    Figure 0007645360000004
  • Figure 0007645360000005
    Figure 0007645360000005
Patent Text Reader

Abstract

The cemented carbide according to one non-limiting aspect of the present disclosure has a plurality of tungsten carbide particles and a bonded phase that contains at least Co. The bonded phase furthermore contains Cr. In a cross-section of the cemented carbide, a region in which a facing-surface length L of 100 nm or greater is maintained and in which the distance X between surfaces of adjacent tungsten carbide particles is 5 nm or less is designated as a WC / WC region. The Cr / Co ratio is greater than 1, where the Cr / Co ratio is the ratio (Cr value / Co value) of a Cr value and a Co value, the Cr value being the peak value of the atomic concentration of Cr obtained through elemental analysis of the WC / WC region in a direction crossing from one tungsten carbide particle across to the other tungsten carbide particle, and the Co value being the peak value of the atomic concentration of Co. A cutting tool based on a non-limiting aspect of the present disclosure has the aforementioned cemented carbide.
Need to check novelty before this filing date? Find Prior Art

Description

CROSS-REFERENCE TO RELATED APPLICATIONS

[0001] This application claims priority to Japanese Patent Application No. 2021-051057, filed on March 25, 2021, the entire disclosure of which is incorporated herein by reference. [Technical field]

[0002] The present disclosure relates to hardmetals and cutting tools. [Background technology]

[0003] As a cemented carbide used for cutting tools, for example, the cemented carbide described in International Publication No. 2019 / 138599 (Patent Document 1) is known. The cemented carbide described in Patent Document 1 has a hard phase consisting of tungsten carbide particles and a binder phase containing Co and Cr. In the region disclosed in Patent Document 1 where the distance between the surfaces of adjacent tungsten carbide particles is 5 nm or less, the maximum value of the ratio C(R) / C(C) of the peak value C(C) of the atomic concentration of Co to the peak value C(R) of the atomic concentration of Cr is 0.177 shown in sample D3 in Table 4. It is known that the solid solubility limit of Cr in Co is approximately 30 atm%, and Patent Document 1 discloses that Co and about half the solubility limit of Cr are present between tungsten particles. Summary of the Invention

[0004] A cemented carbide according to a non-limiting aspect of the present disclosure has a plurality of tungsten carbide particles and a binder phase containing at least Co. The binder phase further contains Cr. In the cross section of the cemented carbide, a region in which the distance X between the surfaces of adjacent tungsten carbide particles having an opposing surface length L of 100 nm or more is 5 nm or less is defined as a WC / WC region. When the maximum value (atm%) of Cr obtained by elemental analysis in a direction transverse from one tungsten carbide particle to the other tungsten carbide particle is defined as the Cr value, the maximum value (atm%) of Co is defined as the Co value, and the ratio of the Cr value to the Co value (Cr value / Co value) is defined as the Cr / Co ratio, the Cr / Co ratio is greater than 1.0.

[0005] A cutting tool according to one non-limiting aspect of the present disclosure comprises the above-described cemented carbide. [Brief description of the drawings]

[0006] [Figure 1] FIG. 2 is a cross-sectional view of a cemented carbide according to one non-limiting aspect of the present disclosure. [Diagram 2] FIG. 1 is a perspective view of a cutting tool according to one non-limiting aspect of the present disclosure. [Diagram 3] 3 is a cross-sectional view taken along line III-III of the cutting tool shown in FIG. 2. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0007] <Cemented carbide> Hereinafter, the cemented carbide 1 of one aspect of the present disclosure will be described in detail with reference to the drawings. However, in the drawings referred to below, for the convenience of explanation, only the main members necessary for explaining the embodiment are shown in a simplified manner. Therefore, the cemented carbide 1 may include any component members not shown in the referenced drawings. In addition, the dimensions of the components in the drawings do not faithfully represent the dimensions of the actual components and the dimensional ratios of each component. These points are also true for the cutting tool described later.

[0008] The cemented carbide 1 may have a plurality of tungsten carbide (WC) particles. The WC particles may also be referred to as hard particles. The cemented carbide 1 may have a hard phase including a plurality of WC particles. The hard phase may include at least one selected from the group consisting of carbides, nitrides, and carbonitrides of metals in Groups 4, 5, and 6 of the periodic table other than WC.

[0009] The average particle size of the WC particles is not limited to a specific value. For example, the average particle size of the WC particles may be 0.5 μm or more and 3.0 μm or less. The average particle size of the WC particles may be measured by image analysis. In this case, the circle equivalent diameter may be the average particle size of the WC particles.

[0010] The cemented carbide 1 may have a binder phase containing at least Co (cobalt). The binder phase may have a function of binding adjacent WC particles together. The binder phase may also have a function of binding adjacent hard phases together.

[0011] The binder phase may further contain Cr (chromium). The content (mass%) of Cr contained in the binder phase may be taken as the Cr content. The Cr content may be 5 mass% or more. When the Cr content is 5 mass% or more, the cemented carbide 1 has high high-temperature hardness and high-temperature strength. The upper limit of the Cr content is not limited to a specific value. For example, the upper limit of the Cr content may be 15 mass%. The Cr content may be measured by ICP (Inductively Coupled Plasma) analysis.

[0012] As a non-limiting example shown in FIG. 1, a region in a cross section of cemented carbide 1 where the distance X between the surfaces of adjacent WC particles (a first WC particle 3 and a second WC particle 5) having an opposing surface length L of 100 nm or more is 5 nm or less may be defined as a WC / WC region S.

[0013] The opposing surface length L may mean the length of the surfaces of adjacent WC particles facing each other in the cross section of the cemented carbide 1. The upper limit of the opposing surface length L is not limited to a specific value.

[0014] The lower limit of the distance X is not limited to a specific value. For example, the lower limit of the distance X may be 0 nm. That is, in the WC / WC region S, adjacent WC particles may be at least partially in contact with each other. The distance X may be constant over the entire length of the WC / WC region S. Note that "constant" may mean roughly constant, and does not necessarily mean constant in the strict sense.

[0015] The WC / WC region S may be subjected to elemental analysis in a direction transverse from one WC particle (first WC particle 3) to the other WC particle (second WC particle 5). The elemental analysis may be performed, for example, by energy dispersive spectroscopy (EDS).

[0016] The maximum value (atm%) of Cr obtained by elemental analysis may be taken as the Cr value, and the maximum value (atm%) of Co may be taken as the Co value. Also, the ratio of the Cr value to the Co value (Cr value / Co value) may be taken as the Cr / Co ratio.

[0017] Here, the Cr / Co ratio may be greater than 1.0. In this case, the strength reduction at high temperatures is small. To be more specific, when Cr is present in the WC / WC region S in a larger amount than Co, it is presumed that the high-temperature properties such as hardness and strength of the WC / WC region S are high, and the strength reduction of the cemented carbide 1 at high temperatures is suppressed. Therefore, the propagation of cracks due to impact at high temperatures is easily suppressed. In the cemented carbide 1, Cr dissolved in the binder phase segregates or precipitates in the WC / WC region S during the cooling process, and since Cr is present in the WC / WC region S in a relatively larger amount than Co, the adhesive strength between the WC particles facing each other through the WC / WC region S is high, so that the strength reduction is suppressed even at high temperatures. Note that since the ratio of Cr to Co present in the WC / WC region S exceeds the solid solubility limit, Cr may exist in the form of carbides, etc.

[0018] Here, high temperature may mean 600° C. or higher and 1000° C. or lower. The presence of Cr in the WC / WC region S in a relatively larger amount than Co may be confirmed by, for example, cross-sectional observation using an EDS attached to an electron microscope. Examples of the electron microscope include a scanning electron microscope (SEM) and a transmission electron microscope (TEM).

[0019] The Cr / Co ratio may be 1.2 or more. In this case, it is estimated that the high-temperature properties such as hardness and strength of the WC / WC region S are further increased, and the strength decrease of the cemented carbide 1 at high temperatures is further suppressed. The upper limit of the Cr / Co ratio is not limited to a specific value. For example, the upper limit of the Cr / Co ratio may be 2.5.

[0020] The Cr value may be 4 atm% or more. In this case, the strength of the cemented carbide 1 is prevented from decreasing at high temperatures, and the growth of cracks due to impact at high temperatures is easily prevented. The upper limit of the Cr value is not limited to a specific value. For example, the upper limit of the Cr value may be 8 atm%.

[0021] The Co value may be 1 atm % or more and 10 atm % or less.

[0022] The binder phase may contain Co in a proportion of 85% by mass or more and 92% by mass or less. In this case, the cemented carbide 1 has a good balance between high-temperature strength and high-temperature hardness, and is suitable for machining difficult-to-cut materials and high-speed machining. The content (% by mass) of Co contained in the binder phase may be taken as the Co content. The Co content may be measured in the same manner as the Cr content.

[0023] The binder phase may further contain W (tungsten). The content (mass%) of W contained in the binder phase may be taken as the W content. As described above, the content (mass%) of Cr contained in the binder phase may be taken as the Cr content. The ratio of the Cr content to the W content (Cr content / W content) may be 1.2 or more and 2.0 or less.

[0024] When the mass ratio of Cr to W contained in the binder phase (Cr content / W content) is 1.2 or more and 2.0 or less, the melting point of the binder phase is low, so that the sinterability is improved and the room temperature strength of the cemented carbide 1 is likely to be improved. The ratio of Cr content to W content (Cr content / W content) may be 1.40 or more and 1.85 or less. The W content may be 3.0 mass% or more and 5.0 mass% or less. The W content may be measured in the same manner as the Cr content.

[0025] The cemented carbide 1 may have a thermal conductivity of 70 W / m·K or more. When this cemented carbide 1 is used as a cutting tool, the effects of thermal shock caused by sudden temperature changes during processing are easily alleviated. In particular, deterioration of mechanical properties caused by significant temperature changes at the cutting edge of the tool is suppressed, and excellent cutting performance can be achieved in high-speed, high-efficiency processing.

[0026] The upper limit of the thermal conductivity is not limited to a specific value. For example, the upper limit of the thermal conductivity may be 90 W / m·K. The thermal conductivity may be measured by a laser flash method. The measurement conditions may conform to JIS R1611 2010.

[0027] <Method of manufacturing cemented carbide> Next, a non-limiting method for producing a cemented carbide according to the present disclosure will be described using the case of producing the cemented carbide 1 as an example.

[0028] First, WC powder, Co powder, and Cr3C2 powder may be prepared as raw material powders. The ratios and average particle sizes of the raw material powders may be set, for example, as follows. The ratio of WC powder may be 86 mass% or more and 95 mass% or less. The ratio of Co powder may be 5 mass% or more and 11 mass% or less. The ratio of Cr3C2 powder may be 0.4 mass% or more and 1.5 mass% or less.

[0029] The average particle size of the WC powder may be 0.4 μm or more and 3.0 μm or less. The average particle size of the Co powder may be 0.5 μm or more and 3.0 μm or less. The average particle size of the Cr3C2 powder may be 0.5 μm or more and 3.5 μm or less. The average particle size of the raw material powder may be a value measured by a microtrack method.

[0030] The prepared raw material powders may be mixed and molded to obtain a molded body. Examples of the molding method include press molding, casting, extrusion molding, and cold isostatic pressing.

[0031] The obtained molded body may be subjected to a binder removal treatment and then fired. The firing may be performed in a vacuum of 0.5 Pa or more and 100 Pa or less. The firing temperature may be 1350° C. or more and 1550° C. or less. The firing time may be 30 minutes or more and 180 minutes or less.

[0032] After firing, the cemented carbide 1 may be cooled to obtain it. Generally, in a vacuum, the cooling is started by turning off the heater while the temperature is kept at a high temperature. However, under such cooling conditions, the Cr / Co ratio does not exceed 1.0. When producing the cemented carbide 1, the cemented carbide 1 may be cooled by controlling the cooling rate to 5°C / min or more and 30°C / min or less after holding at the maximum temperature in firing. Holding at the maximum temperature is also called a first hold. In addition, a second hold may be provided in the cooling stage, in which the temperature is kept in the range of 1150°C or more and 1350°C or less for 0.5 hours or more and 3 hours or less. Furthermore, a mixed gas of N2 gas, Ne gas, He gas, and Ar gas may be introduced between the first hold and the second hold, and when the temperature drops to the second hold temperature, degassing may be performed again and the pressure may be set to 100 Pa or less.

[0033] In addition, in general, the cemented carbide 1 is often cooled while the gas atmosphere (autogenous atmosphere) generated from the compact during firing remains. When producing the cemented carbide 1, a mixed gas of N2 gas, Ne gas, He gas, and Ar gas may be introduced during cooling, degassed again, and the pressure may be set to 100 Pa or less to suppress the autogenous atmosphere. This makes it easy for the autogenous atmosphere containing a large amount of CO gas in the furnace to become uniform and thin. As a result, it is considered that the influence of the autogenous gas (the influence of CO gas) on the cemented carbide 1 is suppressed, the C concentration in the binder phase of the cemented carbide 1 decreases, and the W content and Cr content in the binder phase tend to increase.

[0034] By adjusting the solid-liquid coexistence time of the binder phase by controlling the cooling rate, the secondary keep temperature / time, and the autogenous atmosphere, the Cr content in the WC / WC region S is likely to be increased. In addition, when the secondary keep temperature during cooling is set to a temperature between 10°C and 100°C, which is the lower limit of the liquidus temperature of the binder phase, the ratio of the Cr content to the W content in the binder phase (Cr content / W content) is likely to be adjusted to 1.2 or more and 2.0 or less. Furthermore, by adjusting the particle size of the WC powder used, the thermal conductivity of the cemented carbide 1 is likely to be 70 W / m·K or more. When WC powder with an average particle size of 0.45 μm is used as a raw material, the particle size of the WC particles in the obtained sintered body is 0.8 μm or less under the above firing conditions, and it is difficult to obtain a thermal conductivity of 70 W / m·K or more. The raw material WC powder used may have an average particle size of 1 μm or more.

[0035] The above manufacturing method is one example of a method for manufacturing the cemented carbide 1. Therefore, it goes without saying that the cemented carbide 1 is not limited to those manufactured by the above manufacturing method.

[0036] <Cutting tools> Next, a non-limiting one-sided cutting tool 101 according to the present disclosure will be described with reference to FIGS. 2 and 3. FIG.

[0037] The cutting tool 101 may have a cemented carbide 1. In this case, the strength of the cemented carbide 1 at high temperatures decreases little, so that it is possible to perform stable cutting over a long period of time. The cutting tool 101 may have the cemented carbide 1 as a base.

[0038] The cutting tool 101 may have a coating film 103 that covers at least a part of the surface of the cemented carbide 1. In this case, the cutting tool 101 may have high wear resistance and the like. The coating film 103 may be formed by, for example, a chemical vapor deposition (CVD) method or a physical vapor deposition (PVD) method. The coating film 103 may have a single layer configuration, or may have a configuration in which multiple layers are laminated. The composition of the coating film 103 may include, for example, titanium carbide (TiC), titanium nitride (TiN), titanium carbonitride (TiCN), titanium carbonate nitride (TiCNO), and alumina (Al2O3).

[0039] The thickness of the coating film 103 is not limited to a specific thickness. For example, the thickness of the coating film 103 may be set to about 1 μm or more and 30 μm or less. The thickness of the coating film 103 may be measured by cross-sectional observation using an electron microscope.

[0040] 2 and 3, a cutting insert is shown as a non-limiting example of the cutting tool 101. It should be noted that the cutting tool 101 is not limited to the cutting insert.

[0041] The cutting tool 101 may have a first surface 105 (top surface), a second surface 107 (side surface) adjacent to the first surface 105, and a cutting edge 109 located on at least a portion of the ridge between the first surface 105 and the second surface 107.

[0042] The first surface 105 may be a rake face. The first surface 105 may be a rake face over its entirety, or a part of it may be a rake face. For example, a region of the first surface 105 along the cutting edge 109 may be a rake face.

[0043] The second surface 107 may be a flank. The entire surface of the second surface 107 may be a flank, or a part of the second surface 107 may be a flank. For example, a region of the second surface 107 along the cutting edge 109 may be a flank.

[0044] The cutting edge 109 may be located on a part of the ridgeline, or may be located on the entire ridgeline. The cutting edge 109 can be used to cut a workpiece.

[0045] The cutting tool 101 may have a through hole 111. The through hole 111 can be used to attach a fixing screw or a clamp member when the cutting tool 101 is held in a holder. The through hole 111 may be formed from the first surface 105 to a surface (lower surface) located opposite the first surface 105, and may open in these surfaces. Note that there is no problem even if the through holes 111 are configured to open in opposing regions of the second surface 107.

[0046] The cutting tool 101 may have a rectangular plate shape. The shape of the cutting tool 101 is not limited to a rectangular plate shape. For example, the first surface 105 may have a triangular, pentagonal, hexagonal, or circular shape. The cutting tool 101 may have a columnar shape.

[0047] The cutting tool 101 is not limited to a specific size. For example, the length of one side of the first surface 105 may be set to about 3 mm or more and 20 mm or less. In addition, the height from the first surface 105 to the surface (lower surface) located on the opposite side of the first surface 105 may be set to about 5 mm or more and 20 mm or less.

[0048] The above provides examples of one side of the cemented carbide 1 and cutting tool 101 of the present disclosure that are not limited to the above embodiments, but it goes without saying that the present disclosure is not limited to the above embodiments and may be any as long as it does not deviate from the gist of the present disclosure.

[0049] For example, in the above non-limiting embodiment, the cemented carbide 1 is used in the cutting tool 101, but the cemented carbide 1 can be used in other applications. Examples of other applications include wear-resistant parts such as sliding parts and dies, tools such as drilling tools and blades, and impact-resistant parts.

[0050] The present disclosure will be described in detail below with reference to examples, but the present disclosure is not limited to the following examples. EXAMPLES

[0051] [Sample No. 1-23] <Preparation of cemented carbide> First, the raw material powders shown in the mixed composition column of Table 1 were prepared. The average particle size of the raw material powders was measured by the Microtrack method. The prepared raw material powders were mixed in the combinations and ratios shown in Table 1 to obtain mixed raw material powders.

[0052] Next, the mixed raw material powder was press-molded into a cutting tool shape (CNMG120408, PNMU1205) to obtain a green body. The obtained green body was subjected to a binder removal treatment and held at 1400°C for 1 hour in a vacuum of 0.5 Pa or more and 100 Pa or less.

[0053] After holding at 1400°C, the material was cooled under the cooling conditions shown in the cooling treatment column of Table 1 and under autogenous atmosphere control to obtain a cemented carbide (substrate). The cutting edge (first surface) of the obtained cemented carbide was treated by brushing (R honing).

[0054] [Table 1]

[0055] <Evaluation> The average particle size, content, elemental analysis, and thermal conductivity of the obtained cemented carbide were measured. In addition, cutting evaluation was performed to evaluate the chipping resistance. The measurement method is shown below, and the results are shown in Table 2.

[0056] (Average particle size of WC particles) The average particle size of WC particles was measured by the following procedure. First, a cross section of the WC-based cemented carbide was observed at a magnification of 3000 to 5000 times using a scanning electron microscope (SEM) to obtain an SEM image. At least 50 WC particles, preferably 100 or more WC particles, were identified and extracted from the SEM image. Then, the average particle size of the WC particles was obtained by calculating the circle equivalent diameter using image analysis software ImageJ (1.52).

[0057] (Content) The composition of the metal elements in the binder phase contained in the cemented carbide was analyzed by ICP analysis, and the content of each metal element (Cr content, Co content, and W content) relative to the total amount of metal elements was calculated. In addition, the ratio (Cr content / W content) was calculated using the Cr content and W content. The ICP analysis was performed according to the following procedure. First, the cemented carbide was crushed. Next, 0.2 g was weighed out from the crushed cemented carbide powder. Then, it was dissolved in acid using a solution in which 1 part HCl was added by volume to 1 part water. The acid dissolution was performed by stirring with a stirrer for 24 hours while maintaining the solution at 70°C. Then, the filtered solution was used for ICP analysis. The measurement device used was an ICP emission spectrometer PQ9000Elite (manufactured by Analytik Jena).

[0058] (Elemental analysis) In the cross section of the cemented carbide, a region in which the distance X between the surfaces of adjacent WC particles having an opposing surface length L of 100 nm or more and a distance X between the surfaces of the adjacent WC particles of 5 nm or less was defined as a WC / WC region.

[0059] This WC / WC region was subjected to elemental analysis in a direction crossing from one WC particle to the other WC particle to obtain Cr and Co values. The Cr / Co ratio was calculated using the obtained Cr and Co values. Using the same method, elemental analysis was also performed on three or more other WC / WC regions to determine the average values ​​of the obtained Cr values, Co values, and Cr / Co ratios. An example of the measuring equipment and measuring conditions used for the TEM and TEM-EDS analyses is shown below. ·Device FIB: Focused ion beam processing and observation device JIB-4700F (manufactured by JEOL Ltd.) TEM: Transmission / scanning electron microscope JEM-ARM200F (manufactured by JEOL) EDS: Energy dispersive X-ray spectrometer JED-2300T (manufactured by JEOL) ·conditions FIB processing...Accelerating voltage: 30, 3kV Deposition film: C Sample pretreatmentC deposition TEM analysis: Acceleration voltage: 200 kV EDS analysis: Acceleration voltage: 200 kV Irradiation current amount: Approx. 68pA Measurement time: 30sec / point

[0060] (Thermal Conductivity) Measurements were performed by the laser flash method using a model LFA-502 manufactured by Kyoto Electronics Manufacturing Co., Ltd. The measurement conditions were in accordance with JIS R1611 2010.

[0061] (Cutting evaluation) The cutting performance test was carried out under the following conditions. (1) Fracture resistance test Work material: Heat-resistant cast steel SCH12 square bar Tool shape: PNMU1205ANER-GM Cutting speed: 150m / min Feed rate: 0.30mm / rev Cutting depth: ap=2.0mm ae=50mm Coolant: Dry Evaluation item: Measure the machining time (machining life) until the maximum tool damage width becomes 0.2 mm or more. (2) Abrasion resistance test Work material: Heat-resistant cast steel SCH12 square bar Tool shape: PNMU1205ANER-GM Cutting speed: 200m / min Feed rate: 0.20mm / rev Cutting depth: ap=2.0mm ae=50mm Coolant: Dry Evaluation item: Measure the machining time (machining life) until the maximum tool damage width becomes 0.2 mm or more.

[0062] [Table 2]

[0063] All of Samples Nos. 1 to 5 and 7 to 19, which are the cemented carbide of the present disclosure, were excellent in fracture resistance and wear resistance. [Explanation of symbols]

[0064] 1. Carbide alloy 3. First tungsten carbide particles 5. Secondary tungsten carbide particles 101...Cutting tools 103...Coating film 105...1st page 107...2nd page 109...Cutting edge 111...Through hole L: Length of opposing faces X...distance S...WC / WC area

Claims

1. A cemented carbide having a plurality of tungsten carbide particles and a binder phase containing at least Co, The binder phase further comprises Cr; In the cross section of the cemented carbide, a distance X between the surfaces of adjacent tungsten carbide particles having an opposing surface length L of 100 nm or more is 5 nm or less, and a region in which the binder phase exists between adjacent tungsten carbide particles is defined as a WC / WC region; When the maximum value (atm %) of Cr obtained by elemental analysis in a direction transverse from one tungsten carbide particle to the other tungsten carbide particle is defined as the Cr value, the maximum value (atm %) of Co is defined as the Co value, and the ratio of the Cr value to the Co value (Cr value / Co value) is defined as the Cr / Co ratio, The Cr / Co ratio is greater than 1.

0.

2. 2. The cemented carbide of claim 1, wherein the Cr / Co ratio is greater than or equal to 1.

2.

3. 3. The cemented carbide according to claim 1, wherein the Cr value is 4 atm % or more.

4. The cemented carbide according to any one of claims 1 to 3, wherein the binder phase contains Co in a proportion of 85 mass% or more and 92 mass% or less.

5. The cemented carbide according to any one of claims 1 to 4, wherein the binder phase contains 5 mass% or more of the Cr.

6. The binder phase further contains W. When the content (mass%) of W contained in the binder phase is defined as the W content, and the content (mass%) of Cr contained in the binder phase is defined as the Cr content, The cemented carbide according to any one of claims 1 to 5, wherein the ratio of the Cr content to the W content (Cr content / W content) is 1.2 or more and 2.0 or less.

7. The cemented carbide according to any one of claims 1 to 6, wherein the cemented carbide has a thermal conductivity of 70 W / m·K or more.

8. A cutting tool comprising the cemented carbide according to any one of claims 1 to 7.

9. The cutting tool of claim 8 , further comprising a coating covering at least a portion of a surface of the cemented carbide.

Citation Information

Patent Citations

  • Cemented carbide, and production method therefor

    JP2003105459A

  • Cemented carbide and drill using it

    JP2004256852A

  • Surface-coated cutting tool made from WC-base cemented carbide

    JP2011195846A

  • Cutting tool

    WO2014132512A1

  • Super-hard alloy and cutting tool

    WO2019138599A1